ANALISIS PENGARUH PELATIHAN ROBOT LINE FOLLOWER DAN LAMPU IOT DALAM MENINGKATKAN MINAT STEM SISWA SMA - Junita, Junita; Uranus, Henri P.; Kanalebe, Herman; A.R, M. Gracio; Pardede, Marincan; Mangunsong, Rianto; Yulian, Dwi Heri; Prafo, Salfatore Yan; Susanto, Kathleen Gabriella; Yapply, Legolas (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
This analysis aims to compare the effectiveness of two Community Service (PkM) activities in increasing high school students' interest in STEM (Science, Technology, Engineering, and Mathematics). The activities compared include line follower robot training and IoT (Internet of Things) light-making training. Both activities were designed to provide practical understanding and hands-on experience for students in the field of technology and engineering. This study used an experimental method by comparing students' perceptions of STEM before and after the training. The results of this analysis show that IoT light training was overall more effective in increasing students' interest in the Electrical Engineering program, with a positive perception increase of 58% in the "fun" category and a reduction in negative perceptions by 53%. Meanwhile, the line follower robot training showed a 37% increase in "fun" perception and a 39% decrease in the "not fun" perception. However, line follower robot training was more successful in improving students' technical understanding and skills, with an 18% reduction in the "difficult" perception and an 18% increase in the "easy" perception. In contrast, IoT light training saw a 4% decrease in the "easy" perception and a 1% increase in the "difficult" perception. This difference indicates that both types of training have their respective strengths in shaping students' interest and skills in STEM fields, and a training program that combines aspects of both approaches might yield more optimal results.